EXAMINATION THE CONTENT OF MUSICTHEORY.NET, WHICH IS A FIELD OF STUDY FOR MUSIC THEORY AND HEARING EDUCATION - Gürer, Mert; Bilgin, Selçuk (Nilgun SAZAK, 2021)
In this research, it is aimed to examine Musictheory.net, which is one of the worksheets created for musical hearing, reading and writing education, in terms of content and to reveal its usability in this education framework. In today's world where distance education has become widespread, it is important to examine internet-based pages created to improve hearing, reading and writing skills, and to reveal the usability of such pages in education and assessment and evaluation, as a guide for educators and students. It is also a resource for future studies. This study is a descriptive research and the data obtained in the research were analyzed by content analysis method. Topics such as how the exercises in the relevant worksheet appear in terms of content, their features, the use of the exercises and the suitability for measurement and evaluation have been examined. This worksheet is analyzed in six sections. The first five exercises are about musical hearing and theory, and the last section was created to personalize these exercises according to the readiness of the students and to make assessment and evaluation as a result of the exercises. As a result of these, the importance of this and similar worksheets in terms of facilitating the students to practice, regardless of time and place, has been pointed out, and their positive and negative features are presented under the title of results and suggestions. © 2021, Nilgun SAZAK. All rights reserved.
MÜZİK TEORİSİ VE İŞİTME EĞİTİMİNE YÖNELİK ÇALIŞMA SAYFASI MUSICTHEORY.NET’İN İÇERİK YÖNÜNDEN İNCELENMESİ
Keywords: Music Education; Music Technology; Music Theory; Musical Hearing